The force and stiffness of myosin motors in the isometric twitch of a cardiac trabecula and the effect of the extracellular calcium concentration. (27th May 2018) - Pinzauti, Francesca; Pertici, Irene; Reconditi, Massimo; Narayanan, Theyencheri; Stienen, Ger J. M.; Piazzesi, Gabriella; Lombardi, Vincenzo; Linari, Marco; Caremani, Marco
Abstract : Key points: Fast sarcomere‐level mechanics in intact trabeculae, which allows the definition of the mechano‐kinetic properties of cardiac myosin in situ, is a fundamental tool not only for understanding the molecular mechanisms of heart performance and regulation, but also for investigating the mechanisms of the cardiomyopathy‐causing mutations in the myosin and testing small molecules for therapeutic interventions. The approach has been applied to measure the stiffness and force of the myosin motor and the fraction of motors attached during isometric twitches of electrically paced trabeculae under different extracellular Ca 2+ concentrations. Although the average force of the cardiac myosin motor (∼6 pN) is similar to that of the fast myosin isoform of skeletal muscle, the stiffness (1.07 pN nm –1 ) is 2‐ to 3‐fold smaller. The increase in the twitch force developed in the presence of larger extracellular Ca 2+ concentrations is fully accounted for by a proportional increase in the number of attached motors. Abstract: The mechano‐kinetic properties of the cardiac myosin were studied in situ, in trabeculae dissected from the right ventricle of the rat heart, by measuring the stiffness of the half‐sarcomere both at the twitch force peak ( T p ) of an electrically paced intact trabecula at different extracellular Ca 2+ concentrations ([Ca 2+ ]o ), and in the same trabecula after skinning and induction of rigor. Taking into account the contribution of filament compliance to half‐sarcomere compliance and the lattice geometry, we found that the stiffness of the cardiac myosin motor is 1.07 ± 0.09 pN nm –1, which is slightly larger than that of the slow myosin isoform of skeletal muscle (0.6‐0.8 pN nm –1 ) and 2‐ to 3‐fold smaller than that of the fast skeletal muscle isoform. The increase in T p from 61 ± 4 kPa to 93 ± 9 kPa, induced by raising [Ca 2+ ]o from 1 to 2.5 mm at sarcomere length ∼2.2 μm, is accompanied by an increase of the half‐sarcomere stiffness that is explained by an increase of the fraction of actin‐attached motors from 0.08 ± 0.01 to 0.12 ± 0.02, proportional to T p . Consequently, each myosin motor bears an average force of 6.14 ± 0.52 pN independently of T p and [Ca 2+ ]o . The application of fast sarcomere‐level mechanics to intact trabeculae to define the mechano‐kinetic properties of the cardiac myosin in situ represents a powerful tool for investigating cardiomyopathy‐causing mutations in the myosin motor and testing specific therapeutic interventions. Key points: Fast sarcomere‐level mechanics in intact trabeculae, which allows the definition of the mechano‐kinetic properties of cardiac myosin in situ, is a fundamental tool not only for understanding the molecular mechanisms of heart performance and regulation, but also for investigating the mechanisms of the cardiomyopathy‐causing mutations in the myosin and testing small molecules for therapeutic interventions. The approach has been applied to measure the stiffness and force of the myosin motor and the fraction of motors attached during isometric twitches of electrically paced trabeculae under different extracellular Ca 2+ concentrations. Although the average force of the cardiac myosin motor (∼6 pN) is similar to that of the fast myosin isoform of skeletal muscle, the stiffness (1.07 pN nm –1 ) is 2‐ to 3‐fold smaller. The increase in the twitch force developed in the presence of larger extracellular Ca 2+ concentrations is fully accounted for by a proportional increase in the number of attached motors.